Adrenal crisis secondary to bilateral adrenal haemorrhage after hemicolectomy. (25th October 2016) - Logaraj, Anthony; Tsang, Venessa H M; Kabir, Shahrir; Ip, Julian C Y
Summary: Adrenal haemorrhage is a rare cause of adrenal crisis, which requires rapid diagnosis, prompt initiation of parenteral hydrocortisone and haemodynamic monitoring to avoid hypotensive crises. We herein describe a case of bilateral adrenal haemorrhage after hemicolectomy in a 93-year-old female with high-grade colonic adenocarcinoma. This patient's post-operative recovery was complicated by an acute hypotensive episode, hypoglycaemia and syncope, and subsequent computed tomography (CT) scan of the abdomen revealed bilateral adrenal haemorrhage. Given her labile blood pressure, intravenous hydrocortisone was commenced with rapid improvement of blood pressure, which had incompletely responded with fluids. A provisional diagnosis of hypocortisolism was made. Initial heparin-induced thrombocytopenic screen (HITTS) was positive, but platelet count and coagulation profile were both normal. The patient suffered a concurrent transient ischaemic attack with no neurological deficits. She was discharged on a reducing dose of oral steroids with normal serum cortisol levels at the time of discharge. She and her family were educated about lifelong steroids and the use of parenteral steroids should a hypoadrenal crisis eventuate. Learning points: Adrenal haemorrhage is a rare cause of hypoadrenalism, and thus requires prompt diagnosis and management to prevent death from primary adrenocortical insufficiency. Mechanisms of adrenal haemorrhage include reduced adrenal vascular bed capillary resistance, adrenal vein thrombosis, catecholamine-related increased adrenal blood flow and adrenal vein spasm. Standard diagnostic assessment is a non-contrast CT abdomen. Intravenous hydrocortisone and intravenous substitution of fluids are the initial management. A formal diagnosis of primary adrenal insufficiency should never delay treatment, but should be made afterwards.